Ioannes Kimbar’s Funebria (1603): The Background, the Author, and the Work - Nedzinskaitė, Živilė (Senoji Lietuvos literatūra, 2020)
The article presents the funerary work Funebria in exequias illustris matronae matronae dominae Isabellae Bonarellae de Rovere, coniugis laudatissimae illustris viri d[omi]ni Theodori Laczki, Magni Ducatus Lithuaniae stipendiorum diribitori, Pentacosiarchoque serenissimae Poloniae et Sueciae maiestatis by Ioannes Kimbar, which was published at the print shop of Jan Karcan in 1603. It was written one year after the death and on the occasion of the funeral of Isabella Bonarelli-Laczki (1567–1602), the wife of Teodor Lacki (Theodor Laczki, 1554 – 1610), the field (military) scribe of the Grand Duchy of Lithuania. The work is important for the literary history of the Grand Duchy of for several reasons: its rarity (the Wroblevski Library of the Lithuanian Academy of Sciences holds the only so far known copy of this work), the occasion of its writing (there are very few funerary works dedicated to women in the literature of the Grand Duchy of Lithuania of the time), the origins of the deceased (there were hardly any noble Italian women married to Lithuanian noblemen in the sixteenth century), the author of the work (there is little information about his life), and the literary and cultural significance of the work itself. The article contains a detailed discussion of the circumstances of the appearance of Funebria and provides facts about the author and his education. As it is focused on the introduction of Funebria as a literary work, special emphasis is placed on the structure of the work, which consists of four parts: (1) the coat of arms of the deceased with an armorial poem, (2) the prose dedication to the four Bonarelli brothers of the deceased, (3) the funeral oration (oratio funebris), and (4) eight funerary verses. In the discussion of the most important features of all four parts, considerable attention is given to the analysis of the poetry part. The composition and structure of Funebria are traditional. Laudatio (eulogy) follows the typical sequence of eulogies: the family and the country of the deceased are remembered at the beginning, then the personal qualities of the deceased are extolled, and, finally, the dignified departure from life and the glory of the good name are emphasised. In mournful works, the words of the comploratio (lamentation) part are often placed in the mouths of the relatives of the deceased. In the text of Funebria, there are two versions of the comploratio: in the funeral oration, it is the author who mourns the deceased and her relatives, while in the poetic section, the words of lamentation are put in the mouth of the orphaned son. Consolatio (consolation) is also traditional: as death cannot be avoided, it is important to lead an honest and honourable life. The form of the consolatio in the poetry part is perhaps a little more interesting: the son is comforted by his deceased mother who does not want to return to this world at all and instructs him on how to live his life. The use of topoi, which are characteristic of funerary works and are mostly taken from classical works, is also traditional: the highly popular image of Parks and the contrast between earthly life as a stormy sea and a dangerous road and the afterlife as a peaceful harbour. The author of the article concludes that Kimbar’s Funebria is a work of a truly high artistic level and fits organically into the still relatively sparse corpus of funerary works of the late sixteenth-early seventeenth centuries in the Grand Duchy of Lithuania. It stands out from it solely for the historical dates related to the Laczki family recorded in this work and for exceptional sensitivity and emotionality of the text. In addition, this literary work is the only surviving memorial not only to Isabella Bonarelli-Lacki, but also to the three deceased Lacki children.